2010
DOI: 10.1101/gr.107680.110
|View full text |Cite
|
Sign up to set email alerts
|

De novo rates and selection of large copy number variation

Abstract: While copy number variation (CNV) is an active area of research, de novo mutation rates within human populations are not well characterized. By focusing on large (>100 kbp) events, we estimate the rate of de novo CNV formation in humans by analyzing 4394 transmissions from human pedigrees with and without neurocognitive disease. We show that a significant limitation in directly measuring genome-wide CNV mutation is accessing DNA derived from primary tissues as opposed to cell lines. We conservatively estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
231
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(246 citation statements)
references
References 60 publications
15
231
0
Order By: Relevance
“…The total number of patients with rare de novo CNVs is 6 out of 375 (1.6%). The de novo rate of 1.6% is slightly elevated compared with the de novo rate per genome/generation described by Itsara et al 33,34 They estimate a de novo rate of large CNVs to be 1.2%. However, these include more prevalent CNVs and not a selected subset.…”
Section: Discussionmentioning
confidence: 69%
“…The total number of patients with rare de novo CNVs is 6 out of 375 (1.6%). The de novo rate of 1.6% is slightly elevated compared with the de novo rate per genome/generation described by Itsara et al 33,34 They estimate a de novo rate of large CNVs to be 1.2%. However, these include more prevalent CNVs and not a selected subset.…”
Section: Discussionmentioning
confidence: 69%
“…The rates of de novo CNV in human have been estimated; for example, one study found that the rate for total genome-wide new large CNVs (>100 Kb) is about 1.2 3 10 À2 per genome per transmission (Itsara et al 2010), and another study reported that most of over 4000 CNVs analyzed had individual rates of ;10 À5 per generation (Fu et al 2010). Our limited analysis revealed that meiosis can rapidly generate CNVs among siblings, producing 21 and 32 CNVs in the two sets of four meiotic products, respectively (Supplemental Table 14).…”
Section: Cnvs Due To Meiotic Reshuffling Of Structural Variantsmentioning
confidence: 99%
“…Consistent with this observation, the odds of a CNV being de novo is linearly proportional to its size with CNVs larger than 1 Mbp being more likely to arise sporadically than inherited from a parent ( Figure 1A). There is compelling evidence, then, that CNVs are under strong purifying selection in the general population [24,26,28]. Remarkably, as much as 8-10% of the general population carries such extremely rare or private CNVs suggesting that they must play an important role in human health.…”
Section: Copy Number Variation In Neurodevelopmental Disordersmentioning
confidence: 99%